2016
DOI: 10.21475/ajcs.2016.10.04.p7156x
|View full text |Cite
|
Sign up to set email alerts
|

Mini-grafting of adult Passiflora edulis Sims f. flavicarpa Deg. scions onto vegetatively propagated adult rootstocks of P. mucronata Lam.

Abstract: The mini-grafting is a nondestructive vegetative propagation method based on grafting apical segments onto adult donor plantsderived rootstocks. Here, we aimed at evaluating the mini-grafting of shoot tips derived from adult Passiflora edulis f. flavicarpa plants (yellow passion fruit) onto vegetatively propagated rootstocks of P. mucronata (sandbank passion fruit). Different shoot tip lengths and the fastening material were assayed. A randomized block experimental design was set up following a 2 × 3 factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
1
9
0
5
Order By: Relevance
“…The metal clip was inferior to the others in the protection of the grafted region due to the oxidation of the material, but the others provided 100% seedling survival at 60 DAG. High compatibility between P. edulis and P. mucronata was observed in the works of Alexandre et al (2013) and Oliari et al (2016). The same was observed by Morgado et al (2015), when grafting P. edulis on P. mucronata, with seedling height values of 74.13 cm at 75 days after grafting; at the moment of planting seedlings with at least 15 cm are recommended.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…The metal clip was inferior to the others in the protection of the grafted region due to the oxidation of the material, but the others provided 100% seedling survival at 60 DAG. High compatibility between P. edulis and P. mucronata was observed in the works of Alexandre et al (2013) and Oliari et al (2016). The same was observed by Morgado et al (2015), when grafting P. edulis on P. mucronata, with seedling height values of 74.13 cm at 75 days after grafting; at the moment of planting seedlings with at least 15 cm are recommended.…”
supporting
confidence: 55%
“…As the graft is composed of stem apexes, its cells are younger (absolute growth rate of 2.5 cm day -1 , in addition to being a tender and very hydrated tissue) and for being meristematic tissue, site of auxin synthesis, they show higher cell division rate. Oliari et al (2016) also observed, at 21 DAM, mitoses only of graft cells.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…A espécie P. mucronata também vem apresentando elevado interesse devido à resistência a algumas doenças e, portanto, torna-se alternativa como porta-enxerto sob P. edulis f. flavicarpa (OLIARI et al, 2016), além do potencial para uso ornamental, com flores brancas que se abrem à noite, e de se mostrar tolerante ao frio, com produção ininterrupta de folhas o ano todo .…”
Section: Introductionunclassified